Innovationsaktivitäten von kmU im verarbeitenden Gewerbe: Was zeichnet Imitatoren und originäre Innovatoren aus? - Volker Zimmermann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This contribution is concerned with the spread of new products in small and medium-sized enterprises in the manufacturing sector. Based on an empirical study it is analyzed according to which factors planned product launches are either genuine market novelties or products that are new from the enterprise's perspective but already offered on the market by other enterprises. It appears that the main difference between imitative and new product innovators is the extent of resources spent in the innovation process. Markets with high competition also force enterprises to produce imitative innovations but give special incentives to develop market novelties.
Keywords: O33; O31; O32; 330; KMU; Innovation; Imitation; Diffusion; Klein- und Mittelunternehmen; Innovationsdiffusion; Imitationswettbewerb; Mittelständische Industrie; Deutschland